INFLUENCE OF FAMILIAL DYSFUNCTION ON THE PSYCHO-PHYSICAL DEVELOPMENT OF CHILDREN AND ADOLESCENTS - M. Y. Belyakova; M. Yu. Belyakova; L. V. Abol’yan (Педиатрическая фармакология)
The article presents results of a theoretical methodological analysis of the problem of familial dysfunction as a factor influencing the mental health of children. It shows that peculiarities of family relationships may play a defining role in the formation of psychosomatic symptoms, change the character of a child’s socialization. It describes the influence of peculiarities of different parenting styles on the psychophysical development of children and adolescents.